2020
DOI: 10.1177/1120700020917125
|View full text |Cite
|
Sign up to set email alerts
|

Defensive antibacterial coating in revision total hip arthroplasty: new concept and early experience

Abstract: Background: Infections remains the most feared complication in total hip arthroplasty (THA). New strategies of PJI prevention includes coating of conventional implants. Defensive Antibacterial Coating (DAC), an antibacterial hydrogel coating made of hyaluronan, poly-D and L-lactide can protect biomaterials as an effective barrier at the time of implantation. In addition, it can be used with topical antibiotics to prevent early colonisation of the implant. Scope: This manuscript describes the detailed function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The mixture is then added directly to the implant surfaces about 10 min after mixing. [11] In vitro studies showed significant reductions in bacteria adhesions when used on a sterile titanium disc after being coated with the DAC hydrogel. [39] Animal studies showed the efficacy of DAC hydrogel loaded with an antibiotic to prevent implant-related infection without affecting the bone healing or osseointegration of the implants.…”
Section: Local Hydrogel Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixture is then added directly to the implant surfaces about 10 min after mixing. [11] In vitro studies showed significant reductions in bacteria adhesions when used on a sterile titanium disc after being coated with the DAC hydrogel. [39] Animal studies showed the efficacy of DAC hydrogel loaded with an antibiotic to prevent implant-related infection without affecting the bone healing or osseointegration of the implants.…”
Section: Local Hydrogel Coatingsmentioning
confidence: 99%
“…They reported two early failures within the first 3 weeks post-revision surgery; the remaining 26 patients did not show signs of reinfection (clinical and laboratory) at the last follow-up, they also reported no implant loosening or ingrowth failure. [11]…”
Section: Local Hydrogel Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies demonstrating its efficiency in preventing different types of implant-induced infections exist, studies with a greater number of patients and longer follow-up are lacking. The limitations of this technique are that it enables the addition of a limited amount of antibiotics and its considerable cost [ 184 ]. In addition, the gel-like structure of DAC ® does not provide the mechanical strength and structural stability required for applications in bone repair, causing its unintentional removal during the surgical procedure.…”
Section: Coating Materials Selectionmentioning
confidence: 99%
“…Another crucial advancement in the treatment plan is introducing new implant coatings (which have prevention and curative roles); local hydrogel coatings showed their efficacy in preventing infection when used with cementless implants to manage patients diagnosed with chronic PJI with no effect on the implant osteointegration properties. [16] Povidone-iodine was used as a coating for hip implants, which resulted in no infection when implanted in revision cases for PJI. [17] Furthermore, silver nanoparticles were used as coatings, which showed promising results regarding reducing the post-operative incidence of PJI.…”
Section: Diagnosismentioning
confidence: 99%